KARAKTERISTIK PENDERITA TUBERKULOSIS PARU PADA BALITA YANG DIRAWAT INAP DI RUMAH SAKIT VITA INSANI PEMATANGSIANTAR TAHUN 2010-2012 - isri rezta; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and one of the lower respiratory track disease. Based on the Profile of Disease Control and Enviromental Sanitation in 2012, the proportion of child TB in North Sumatera is 2,4%. To determine the characteristics of children under five years with pulmonary TB who were hospitalized in Vita Insani Hospital Pematangsiantar within 2010-2012, conducted a descriptive study with case series design. Population and sample was 106 patients. Univariate data were analyzed by descriptive while bivariate data were analyzed by using Chi square test, t-independent, Anova, Kruskal-Wallis and Mann-Whitney. The highest proportion is in the age group 0-<12 month (50,0%), male (58,5%), Bataknese (67,9%), Protestantism (54,7%), came from outer Pematangsiantar (75,5%), with adequate nutritional status (66,0%), have received BCG immunization (81,1%), diagnosis of disease by blood test and X-ray (100,0%), average length of hospitalization 3,11 days (3 days), discharge based on doctor permission (95,3%), using own cost (93,4%). There was no significant difference of age based on nutritional status, there was no significant difference of age based on BCG immunization status, there was no significant difference of sex based on nutritional status, there was no significant difference of sex based on BCG immunization status, there was no significant difference of average length of hospitalization based on nutritional status, there was no significant difference of average length of hospitalization based on the state while come back home, there was no significant difference of average length of hospitalization based on cost source. The writer expects the health workers  to complete the data on the status of patient such as the history of pulmonary TB in family and in the diagnosis of pulmonary TB in children under five years according to national guidelines for prevention of TB.